ImagePy: an open-source, Python-based and platform-independent software package for bioimage analysis - Wang, Anliang; Yan, Xiaolong; Wei, Zhijun (Bioinformatics, 2018)
Abstract Summary This note presents the design of a scalable software package named ImagePy for analysing biological images. Our contribution is concentrated on facilitating extensibility and interoperability of the software through decoupling the data model from the user interface. Especially with assistance from the Python ecosystem, this software framework makes modern computer algorithms easier to be applied in bioimage analysis. Availability and implementation ImagePy is free and open source software, with documentation and code available at https://github.com/Image-Py/imagepy under the BSD license. It has been tested on the Windows, Mac and Linux operating systems.